Condom use behaviours and correlates of use in the Botswana Defence Force. (November 2013) - Tran, Bonnie Robin; Thomas, Anne Goldzier; Ditsela, Mooketsi; Vaida, Florin; Phetogo, Robert; Kelapile, David; Chambers, Christina; Haubrich, Richard; Shaffer, Richard
Preventing HIV infection is a priority for militaries. HIV prevention research is needed to monitor existing programme, identify areas for modification, and develop new interventions. Correct and consistent condom use is highly effective against HIV. However, use among soldiers is lower than ideal. This study describes condom use behaviours and examines correlates of use in the Botswana Defence Force (BDF). Analyses were based on 211 male BDF personnel, aged 18–30, who completed a cross-sectional survey that collected baseline data for an intervention study. Results showed that 51% of participants reported always using condoms, 35% used condoms most times, and 14% used condoms occasionally/never. Condom use varied by partner type and was typically higher with casual partners in comparison to regular partners. After adjustment for age and marital status, factors associated with lower condom use included excessive alcohol use, perception that using condoms reduce sexual pleasure, and having a trusted partner. However, higher levels of HIV knowledge and reports of being circumcised were protective against lower condom use. HIV interventions aimed at increasing condom use in the BDF should address condom perceptions, alcohol abuse, and issues of trust. Innovative ways to increase condom use in this population should also be explored.